Vertical reaction forces and kinematics of backward walking underwater - Carneiro L.C.* (2012)
The aim of this study was to compare the first and second peaks of the vertical ground reaction force (VGRF) and kinematics at initial contact (IC) and final stance (FS) during walking in one of two directions (forward × backward) and two environments (on land × underwater). Twenty-two adults (24.6±2.6 years) walking forward (FW) and backward (BW) on a 7.5 m walkway with a central force plate. Underwater immersion was at the height of the Xiphoid process. Ten trials were performed for each condition giving a total of 40 trials where the VGRF and kinematic data were recorded. Two-way repeated measures analysis of covariance was used with a combination of environment and direction of walking: FW on land, FW underwater, BW on land and BW underwater (entered as between-subjects factor) and repeated measures of VGRF peaks (first and second) or angles (at IC and FS). Walking velocity was included as a covariate. Both VGRF peaks were reduced when participants walked underwater compared to on land (p<.001). For BW, in both environments, the second peak was lower than the first (p<.001; for both). During BW at IC the ankle is more dorsiflexed and the knee is more flexed, both on land and underwater. At FS, there was no difference between the ankle angle for FW and BW in both environments. At IC, in FW and BW the knee and hip are more flexed underwater. BW underwater involves a lower VGRF and more knee and hip flexion than BW on land. © 2011 Elsevier B.V.